Quantifying quality changes in dark purple eggplant as affected by fluctuating storage conditions and wrapping materials - Cortbaoui, Patrick E; Ngadi , Michael O (Journal of Postharvest Technology, 2018)
Produce quality can be irreversibly damaged by exposure to fluctuating temperature and light when moving along the supply chain. Quality loss of fresh fruits and vegetables is of considerable interest due to its omnipresent occurrence, which exceeds 50% in some developing countries. In this work, different storage scenarios and their effect on eggplant quality were investigated. Under isothermal conditions, two temperatures were chosen under partial and complete absence of light. Under non-isothermal storage, four different combinations of temperatures and light were studied. These combinations represented all segments of the supply chain of fresh fruits and vegetables (from the producer to the consumer). At the end of the entire storage duration, the measured quality loss for unwrapped samples were 75.62% for firmness, 11.02% for weight loss, 10.19% for color and 61.11% for quality index. These losses were reduced significantly (P < 0.05) through wrapping the fresh produce during storage and the percent quality loss were as follows: 19.43% for firmness, 0.84% for weight loss, 7.31% for color and 22.22% for quality index. Kinetic models were used to provide a structural framework for quantitatively describing and predicting those losses.